Modeling of transient flows in viscoelastic pipe network with partial blockage - Parvin Chahardah-Cherik (IWA Publishing, 2021)
In this study, transient flow and partial blockage in polyethylene (PE) pipe network are investigated experimentally and numerically using the method of characteristics in the time domain considering pipe-wall viscoelasticity. The experiments were conducted on a PE pipe network with and without partial blockage. The experimental pressure signals were damped during a short period of time in the blockage-free case. The numerical model was calibrated by the inverse transient analysis (ITA). The hydraulic transient solver calibrated with one Kelvin–Voigt element showed good consistency with the experimental results. Partial blockages with different lengths and sizes were examined at different locations of the pipe network. Results reveal an increase in head loss, pressure signal damping, and phase shift with increase in blockage. In addition, the location and characteristics of blockages with different sizes were determined using the ITA in the pipe network. HIGHLIGHTS Experimental investigation of transient flow properties in a viscoelastic pipe network.; The effects of blockage on transient flow were examined in a polymer pipe network.; ITA was used to calibrate the numerical model.; Determining the blockage characteristics in the pipe network.;